Pengaruh Belanja Pendidikan, Belanja Kesehatan Dan Belanja Bantuan Sosial Terhadap Kemiskinan Pada Kabupaten Dan Kota Di Provinsi Jawa Barat - Annisa Marni Melati; Sudradjat; Dian Imanina Burhany (Indonesian Accounting Research Journal, 2021)
This study aims to test and find out how much the effect of education expenditure, health expenditure and social assistance expenditure both partially and simultaneously on the poverty of regencies and cities in West Java Province. The unit of analysis in this study were regencies and cities in West Java Province. The data used in this research is secondary data in the form of regency and city Budget Realization Report in West Java 2015-2019. This research used purposive sampling technique, the sample used in this study consist of 15 regencies and 7 cities in West Java Province. The data analysis method in this studi is panel data regression analysis with the help of the Eviews aplication. The results of this study showed that education expenditure and health expenditure have a negative and significant effect on the poverty level partially, while social assistance expenditure has no significant effect on the poverty level. Simultaneously education expenditure, health expenditure, and social assistance expenditure has a significant effect on the poverty rate of 88,85%, while the remaining 11,15% is explained by other variables outside of this study.